Expert Microsoft Teams solutions : a guide to teams architecture and integration for advanced end-users and administrators - Guilmette, Aaron; Lee, Yura; Oliasani, Grant; Nicholls, Alan (Packt Publishing, 2022)
Written by Microsoft engineers, Expert Microsoft Teams Solutions covers in-depth topics in Teams that are not covered elsewhere and explores tasks that customers frequently rely on Microsoft Partners to accomplish Key Features Extend the MS Teams experience with this practical guide from Microsoft's technical specialists Discover advanced Teams capabilities such as voice, governance, and Power Platform integration Get to grips with planning resources for voice integration in Teams Book Description Microsoft Teams is designed to improve collaboration and integrate components of SharePoint, Exchange, Power Platform, and voice calling into a single platform. Complete with step-by-step explanations of concepts, practical examples, and architecture guidance, you'll learn how to plan and deploy Teams for your organization. As you progress, you'll explore and understand the Teams platform as a whole, from architecture and collaboration through to apps and voice, with the help of examples. The book approaches Teams not only from an end-user perspective but also from an administrator's point of view. You'll be able to understand the challenges around modernization in your organization relating to adopting, implementing, and administering Teams and tackle them effectively. By helping you realize the potential of Teams as a platform, this book will enable you to set up and deploy Teams solutions, leading to modernization in your organization's chat and voice infrastructure. By the end of this book, you'll be able to design and implement the most important and exciting aspects of Microsoft Teams. What you will learn Gain a clear understanding of Microsoft Teams architecture and deployment concepts Become well-versed with advanced Teams voice capabilities Explore best practices to extend the Teams experience to various apps through collaboration Focus on how to conduct effective meetings, including ad hoc, scheduled, channel, and live events Integrate Power Apps and Power Automate with Microsoft Teams Understand key governance and security concepts in administering Microsoft Teams Who this book is for The book is for intermediate-level and experienced Microsoft Teams IT professionals as well as for administrator roles. Intermediate-level knowledge of the Microsoft Teams platform is assumed.